Actualizing Exploratory Practice (EP) principles with team teachers in Japan. (April 2016) - Hiratsuka, Takaaki
Abstract: This paper reports on my personal inquiry in which I adopted Exploratory Practice (EP) to enhance the team-teaching opportunity in the Japan Exchange and Teaching (JET) program. Two pairs of team teachers and their students from two Japanese high schools participated in this EP inquiry, which consisted of multiple activities, including class observations, pair discussions, group discussions, EP story writing and reflective classes. This paper focuses on the experience of the team teachers. Relevant data were analyzed using content analysis. Findings suggest that the teachers came to understand and followed, or 'actualized' seven EP principles involving 'what', 'who' and 'how' issues. Factors affecting EP actualization and implications related to EP studies are discussed.